Multi-omics analyses reveal the biocontrol potential of endophytic Paenibacillus peoriae 3-B4 against maize seedling blight - Hu, Yue; Chen, Yifan; Chao, Shengqian; Zhang, Yin; Song, Lili; Wang, Hui; Hu, Yingxiong; Lv, Beibei (Frontiers in Microbiology, 2025)
IntroductionMaize seedling blight, caused by the phytopathogenic fungus Fusarium verticillioides, is a common and rapidly spreading disease that reduces grain quality and yield. Control of this pathogen is challenging due to its complex infection process and the development of resistance to chemical pesticides. Biological control agents are therefore recognized as a sustainable and environmentally friendly strategy for the maize seedling blight.ResultsIn this study, we isolated and identified Paenibacillus peoriae 3-B4 from maize leaves, which exhibited a 59.92% inhibitory rate against F. verticillioides in greenhouse co-inoculation conditions. Genome sequencing revealed a 5.91 Mb chromosome containing biosynthetic gene clusters involved in antifungal secondary metabolites, along with genes associated with induced systemic resistance (lSR) and pattern-triggered immunity (PTl). Transcriptomic analysis was performed on maize seedling leaves from a greenhouse experiment, identifying 8,997 differentially expressed maize genes, which were primarily enriched in MAPK signaling and plant–pathogen interactions. 16S rRNA analysis further showed significant shifts in microbial communities, particularly an increase in the abundance of beneficial genera such as Paenibacillus, Delftia, and Corynebacterium. The combined analysis of key differentially expressed genes (DEGs) and bacterial community profiles suggested coordinated shifts in host transcriptional responses and microbial abundances following P peoriae 3-B4 treatment.DiscussionThese findings not only emphasize the importance of endophytic bacteria in plant defense, but also provide new insights into the development of sustainable biological control strategies for maize fungal diseases.